Combining 3D-Printed Models and Open Source Molecular Modeling of p53 To Engage Students with Concepts in Cell Biology† - Verónica A. Segarra (American Society for Microbiology, 2020)
While understanding macromolecular structural elements and their roles in dictating cellular function is critical to grasp basic concepts in biology, it can be challenging for students to master this content—these elements naturally exist at the nanoscale and are not observable with the naked eye. Oftentimes this understanding is catalyzed by impactful illustrations and animations found online and in textbooks. In recent years, 3D printing technology has become readily accessible as an additional way to generate models and visualize entities of interest. In this report, we describe and discuss the efficacy of an approach using 3D-printed models in combination with online open-source molecular modeling analyses of the macromolecular structure of p53 to engage students with molecular concepts in cancer cell biology and human health. This pedagogy strategy has been successfully integrated into an upper-level undergraduate course at a primarily undergraduate institution and a graduate biology course at a public research university. We describe the potential benefits while providing tools for others to integrate this strategy into their teaching.